2021
DOI: 10.1016/j.scitotenv.2020.143539
|View full text |Cite
|
Sign up to set email alerts
|

Emerging paradigms of viral diseases and paramount role of natural resources as antiviral agents

Abstract: In the current scenario, the increasing prevalence of diverse microbial infections as well as emergence and re-emergence of viral epidemics with high morbidity and mortality rates are major public health threat. Despite the persistent production of antiviral drugs and vaccines in the global market, viruses still remain as one of the leading causes of deadly human diseases. Effective control of viral diseases, particularly Zika virus disease, Nipah virus disease, Severe acute respiratory syndrome, Coronavirus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 307 publications
0
19
0
2
Order By: Relevance
“…There have been studies on the possible use of natural products to treat or prevent infections by various virus species (for review [396][397][398][399]). For example, studies have shown the anti-viral effects of carvacrol on murine norovirus [400], the effects of α-terpinene, γ-terpinene, α-pinene, p-cymene, terpinene-4-ol, α-terpineol, thymol, citral, and 1,8-cineole on herpes simplex virus type 1 (HSV-1) [401,402] and respiratory syncytial virus (RSV) [403].…”
Section: Terpenes and Other Volatile Phytochemicals With Anti-viral Effectsmentioning
confidence: 99%
“…There have been studies on the possible use of natural products to treat or prevent infections by various virus species (for review [396][397][398][399]). For example, studies have shown the anti-viral effects of carvacrol on murine norovirus [400], the effects of α-terpinene, γ-terpinene, α-pinene, p-cymene, terpinene-4-ol, α-terpineol, thymol, citral, and 1,8-cineole on herpes simplex virus type 1 (HSV-1) [401,402] and respiratory syncytial virus (RSV) [403].…”
Section: Terpenes and Other Volatile Phytochemicals With Anti-viral Effectsmentioning
confidence: 99%
“…Natural products are a rich source of molecules with diverse biological activities; while some natural compounds have been shown to protect against viruses of specific families, others have demonstrated broad-spectrum antiviral activity [16-18]. Drugs derived from natural sources have several advantages over synthetic compounds, among them low cost, fewer side-effects, diversity and complexity of chemical molecules, which may limit viral drug resistance and their cost-effectiveness in drug discovery programs [19]. All these characteristics suggest that screening natural compounds is a promising strategy for identifying new potential antivirals.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence and re-emergence of new infectious diseases especially of viral origin are of great concern to global public health ( Louten, 2016 ; Mourya et al, 2019 ; Abrahão and de Arruda, 2020 ). This has reignited the search for natural compounds especially, from plants as potential sources of new drug candidates to add to the current armamentarium ( Jans et al, 2020 ). This review focusses on HIV-1 and SARS-CoV-2, the viruses that cause AIDs and covid-19 respectively because over the last 50 years, these two viruses have caused huge pandemics globally: the HIV/AIDS pandemic and covid-19 pandemic ( Illanes-Álvarez, et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%